Enhancing Distribution Logistics Services through the Optimization of Ergonomic Concepts: A Case Study Approach - Astutik, Widi; Mujaddid; Fole, Asrul; Safitri, Khoerun Nisa; Kulsaputro, Januar; Musdalifah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study explores the aspects of enhancing distribution logistics services through the optimization of ergonomic concepts, focusing on the critical role of ergonomics in improving employee productivity and safety within the logistics sector. Utilizing a case study methodology, the research identifies key challenges in implementing ergonomic practices, such as high initial costs, resistance to change, and the lack of standardized guidelines. The study proposes actionable solutions for effectively integrating ergonomic concepts into distribution logistics services, aiming to create safer and more comfortable work environments that promote employee satisfaction and efficiency. The findings highlight the potential benefits of ergonomic optimization, including enhanced operational efficiency, reduced workplace injuries, and improved employee well-being, which collectively contribute to a more engaged workforce. This research serves as a foundation for future studies aimed at further enhancing logistics services through ergonomic principles, ultimately contributing to a more sustainable and competitive industry. By prioritizing ergonomics, organizations can foster a culture of safety and well-being that benefits both employees and overall organizational performance. The integration of ergonomic practices not only leads to healthier work environments but also enhances overall productivity, making it a vital consideration for logistics companies striving for excellence in service delivery.